Measurement of equivalence between the web and paper versions of the Japanese Orthopaedic Association Hip Disease Evaluation Questionnaire. Issue 2 (3rd March 2020) - Takegami, Yasuhiko; Seki, Taisuke; Higuchi, Yoshitoshi; Osawa, Yusuke; Ishiguro, Naoki
Abstract: Objectives: Digitised patient-reported outcome may be beneficial for physicians and patients. The Japanese Orthopaedic Association Hip Disease Evaluation Questionnaire (JHEQ) can only be completed with paper and pencil (pJHEQ). We newly developed a web version of the JHEQ (wJHEQ). This study aimed to determine whether the scores obtained with the wJHEQ are equivalent to those from the pJHEQ, how much the wJHEQ would decrease missing answers, and which JHEQ the participants preferred to use. Methods: To measure equivalence between the pJHEQ and wJHEQ, we evaluated the mean score difference for each subscale (pain, movement, mental) and Visual Analogue Scale (VAS; satisfaction, right hip pain, left hip pain) and then assessed the intraclass correlation coefficients (ICC) between the two scores. ICC values ≥0.75 were defined as excellent agreement. We used Bland–Altman analysis to assess level of agreement between the values of the two questionnaires. We compared the number of incomplete forms and amount of missing data between the two questionnaires. We investigated ease of use by asking the participants which format was easier to use. Results: This study comprised 113 patients (mean age 58.1 years, 81% female) with hip disease. Mean score differences for each subscale between the wJHEQ and pJHEQ were not significantly different. The values of ICC for each subscale and each VAS were all >0.75. All 113 participants completed the wJHEQ questionnaire, whereas nine patients did not complete the pJHEQ form. There was a significant statistical difference between the completion rate of the wJHEQ and that of the pJHEQ ( p = .0017). Fifty-seven participants (55%) preferred the wJHEQ, whereas 33 participants (32%) preferred the pJHEQ. Conclusion: The wJHEQ was found to be equivalent to the original pJHEQ. The wJHEQ significantly decreased the numbers of missing answers and incomplete forms. The participants felt ease of use was nearly equivalent. The wJHEQ might help facilitate more complete assessments in clinical trials and research.